Mapping the Wind Energy Potential of Sweden: A Sociotechnical Wind Atlas - Enevoldsen, Peter; Permien, Finn-Hendrik (Journal of Renewable Energy, 2018)
The installation of onshore wind farms has increased in the past decade all over Sweden, and as a result, more wind projects are facing challenges of, for instance, social opposition and lack of space, which potentially complicate resource assessments. As a response to the current challenges in the Swedish wind industry, this study examines and develops a strategic map of potential areas for the construction of new farms in Sweden. The analyses used to prepare the map are performed using a holistic research strategy that focuses on everything from social to technical challenges. The map is based on an extensive data collection consisting of a comprehensive wind dataset mixed with the outcome of large-scale qualitative studies that include five dominant stakeholder groups in the Swedish wind industry and detailed information on restrictive areas. Consequently, this research presents a resource map, which is intended to inspire all stakeholders in the Swedish wind industry to further develop the successful case of wind power in Sweden. Furthermore, the current research aims to update ongoing debates in the wind energy literature, and finally, it introduces a tool that can be used in all phases of a large-scale energy strategy that involves wind power.